The Price of Success: Adaptation or Assimilation? Romanian Officials of Maramureș Under Hungarian and Romanian Rule (1822–1945) - SZABÓ, Zsolt (Studia Universitatis Babeș-Bolyai Historia, 2025)
The study argues that in 19th-century Maramureș, assimilation was not a prerequisite for achieving high office. When it occurred, it largely resulted from adaptive strategies in marriage and education, combined with the dynamics of local politics. Depending on the wider political climate, both Hungarian and Romanian nationalism, as well as the personal interests of the families, could either hasten or counteract these tendencies. The article examines the history and national identity of the Romanian Iurca (Jurka), Man (Mán), Mihalca (Mihálka), and Mihalyi (Mihályi) families of Maramureș through a prosopographical approach. In the Reform Era, these families formed a tightly knit alliance, rallying the Romanian petty nobility in pursuit of their shared goals. Their Hungarus identity further bolstered their political weight during the 1848 – 49 Revolution. In the Dualist period, intermarriage with Hungarian families accelerated their social integration, while they also accumulated estates surpassing those of competing Hungarian landowners. Through pragmatic political agreements with both Hungarian and Romanian governing parties, they not only consolidated their authority but also maintained it through successive regime changes – from the Austro-Hungarian Compromise and the dissolution of the Monarchy to the Second Vienna Award. Rezumat: Studiul argumentează că, în Maramureșul secolului al XIX-lea, asimilarea nu a constituit o condiție esențială pentru ascensiunea profesională. Atunci când a avut loc, ea a fost mai curând rezultatul unor strategii de alianțe matrimoniale, de instruire și de adaptare la contextul politic local, procese care – în funcție de conjunctura politică – puteau fi accelerate sau inversate de naționalismul maghiar ori român, precum și de interesele proprii ale familiilor. Lucrare examinează istoria și transformările identității naționale ale familiilor românești Iurca (Jurka), Man (Mán), Mihalca (Mihálka) și Mihalyi (Mihályi) din Maramureș, utilizând o perspectivă prosopografică. În perioada pașoptistă, aceste familii au format un grup strâns unit, capabil să mobilizeze mica nobilime românească în sprijinul propriilor interese. Apartenența lor la identitatea hungarus le-a sporit influența în timpul revoluției din 1848 – 1849. În epoca dualistă, căsătoriile mixte au facilitat integrarea în societatea maghiară, iar proprietățile funciare acumulate au depășit pe cele ale familiilor maghiare concurente. Prin înțelegeri politice cu partidele aflate la guvernare, atât maghiare, cât și românești, aceste familii și-au consolidat și ulterior și-au menținut poziția de putere în ciuda schimbărilor de regim – de la Compromis, trecând prin Marea Unire, până la cel de-al Doilea Arbitraj de la Viena. Cuvinte-cheie: Maramureș, naționalism, elite studies, prozopografie, funcționari comitatenși